2021
DOI: 10.1088/1674-1056/ac0043
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic phase diagram of single-layer CrBr3 *

Abstract: We theoretically provide a magnetic phase diagram for the single-layer (SL) CrBr3, which could be effectively tuned by both strain engineering and charge doping in SL-CrBr3. Through systematical first-principles calculations and Heisenberg model Hamiltonian simulations, three different magnetic phases in SL-CrBr3, which are off-plane ferromagnetic, in-plane ferromagnetic and in-plane Néel-antiferromagnetic phases, are found in the strain and charge doping regimes we studied. Furthermore, our results show that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Flexible or stretchable nanoparticle films have been expanding rapidly for many years as they promise mechanical properties for functional and conformable materials that can be applied to research fields such as wearable electronic devices and biomedical devices. [1][2][3][4][5][6] For example, flexible metallicoxide-barrier magnetic tunnel-junction devices applied in the flexible electronics field exhibit reliable and stable operation under substantial deformation of the flexible substrates. [7] Increasing numbers of applications are based on the stretchability and flexibility of substrates used for functional nanomaterials.…”
Section: Introductionmentioning
confidence: 99%
“…Flexible or stretchable nanoparticle films have been expanding rapidly for many years as they promise mechanical properties for functional and conformable materials that can be applied to research fields such as wearable electronic devices and biomedical devices. [1][2][3][4][5][6] For example, flexible metallicoxide-barrier magnetic tunnel-junction devices applied in the flexible electronics field exhibit reliable and stable operation under substantial deformation of the flexible substrates. [7] Increasing numbers of applications are based on the stretchability and flexibility of substrates used for functional nanomaterials.…”
Section: Introductionmentioning
confidence: 99%
“…Chromium trihalides have been studied recently, manifesting as a platform for research of magnetic properties in vdW 2D materials, and having a number of unique phenomena. Effects of mechanical deformation were explored theoretically in monolayers CrX 3 samples, [38][39][40][41]. From calculations, it was also shown that mechanical strain mostly influences the angle between the Cr-X-Cr bonds rather than their length, leading to significant distortion of the crystal lattice.…”
Section: Introductionmentioning
confidence: 99%